Evaluación bioeconómica de sistemas de Producción caprina semi-comercial en Costa Rica - Navarro Delgado, Humberto (1983)
Tesis (Mag. Sc.) -- CATIE, Turrialba (Costa Rica) -- UCR, San José (Costa Rica), 1983